Evaluation of Eight-Item Vancomycin Prescribing Confidence Questionnaire Among Junior Doctors - Liu, Lu; Jiang, Zhehan; Xie, Ana; Wang, Weimin (Frontiers in Medicine, 2021)
Background: Assessing the preparedness of junior doctors to use vancomycin is important in medical education. Preparedness is typically evaluated by self-reported confidence surveys. Materials and Methods: An eight-item vancomycin prescribing confidence questionnaire was developed, piloted, and evaluated. The questionnaire responses were collected from 195 junior doctors and a series of statistical techniques, such as principal component analysis and confirmatory factor analysis, and were implemented to examine the validity and reliability. Results: The principal component analysis supported a one-factor structure, which was fed into a confirmatory factor analysis model resulting in a good fit [comparative fit index (CFI) = 0.99, Tucker–Lewis index (TLI) = 0.99, root mean square error of approximation (RMSEA) = 0.08, standardized root mean square residual (SRMR) = 0.04]. Ordinal-based α was 0.95, and various ωs were all above 0.93, indicating a high reliability level. The questionnaire responses were further proved to be robust to extreme response patterns via item response tree modeling. Jonckheere–Terpstra test results (z = 6.5237, p = 3.429e−11) showed that vancomycin prescribing confidence differed based on the experience in order (i.e., four ordinal independent groups: “≤10 times,” “11–20 times,” “21–30 times,” and “≥31 times”) and therefore provided external validity evidences for the questionnaire. Conclusions: The questionnaire is valid and reliable such that teaching hospitals can consider using it to assess junior doctors' vancomycin prescribing confidence. Further investigation of the questionnaire can point to the relationship between the prescribing confidence and the actual performance.